2021
DOI: 10.1002/jcop.22560
|View full text |Cite
|
Sign up to set email alerts
|

Social‐ecological theory, substance misuse, adverse childhood experiences, and adolescent suicidal ideation: Applications for community–academic partnerships

Abstract: Suicide is the second leading cause of death among youth in the United States. Data from the 2015 Youth Risk Behavior Survey of 9th-12th grade students in New Hampshire (N = 14,837) were utilized. Adjusted odds ratios (aORs) and 95% confidence intervals (CIs) were estimated using logistic regression models to evaluate associations between suicidal ideation, adverse childhood experiences (ACEs), and other risk factors including using opioids/drugs without a prescription and food insecurity. We also examined whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 46 publications
0
11
0
1
Order By: Relevance
“…In childhood and adolescence, ELS is not only associated with the heightened risk of adverse health problems [26][27][28][29][30][31][32], including physical illnesses such as headache [33] and asthma [34] but also mental illnesses such as depression, non-suicidal self-injury (NSSI) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. A meta-analysis that examined the association between ELS and depression in adolescents found that the association between childhood abuse/neglect and depression was much stronger in adolescents than in adults [50].…”
Section: Introductionmentioning
confidence: 99%
“…In childhood and adolescence, ELS is not only associated with the heightened risk of adverse health problems [26][27][28][29][30][31][32], including physical illnesses such as headache [33] and asthma [34] but also mental illnesses such as depression, non-suicidal self-injury (NSSI) [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49]. A meta-analysis that examined the association between ELS and depression in adolescents found that the association between childhood abuse/neglect and depression was much stronger in adolescents than in adults [50].…”
Section: Introductionmentioning
confidence: 99%
“…Past researchers using data from the YRBS have reported that suicidality in high school students is associated with female sex ( 2 , 4 ), sexual minority status ( 47 49 ), adverse childhood experiences ( 50 , 51 ), physical teen dating violence ( 52 ), forced sexual intercourse ( 18 , 53 ), body weight perceptions [both overweight ( 54 , 55 ) and underweight ( 55 )], illicit drug use ( 13 , 18 ), prescription opioid misuse ( 56 58 ) [especially in girls ( 59 )], alcohol use ( 15 , 18 , 60 , 61 ), marijuana use ( 13 , 15 , 62 ), bullying ( 18 , 55 , 63 , 64 ) and cyberbullying ( 18 , 55 , 63 65 ), frequent physical fighting ( 66 ), excessive television/video game/internet use ( 67 , 68 ), insufficient sleep ( 69 ), and even soft drink consumption ( 70 ). With so many variables being associated with suicidality in youth—especially given the very large national sample allowing the identification of statistically significant findings with small effect sizes—it is not particularly surprising that concussion was also associated in the present study, in univariate analyses, and in prior studies using the 2013 ( 45 ) and 2017 YRBS ( 41 43 , 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, this study focused mainly on the impacts of parenting styles on adolescents’ depressive symptoms and suicidal ideation. However, according to ecological systems theory [ 89 , 90 ], adolescents’ depressive symptoms and suicidal ideation may act as risk factors to induce parents’ harsh parenting and aggravate the effects of harsh parenting, causing a vicious circle and exacerbating adolescents’ mental health problems [ 1 ]. Therefore, future studies are encouraged to explore the potential interaction process relationships between harsh parenting and adolescent mental health problems.…”
Section: Discussionmentioning
confidence: 99%